The impact of Covid-19 on the banking industry efficiency: Comparison between Indonesia and Malaysian banks - Riani, Ririn; Ikhwan, Ihsanul (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose − This study aims to measure and compare the efficiency of Islamic and conventional banks in Indonesia and Malaysia, from 2015 to 2020.Methodology − Data Envelopment Analysis (DEA) was employed as a research method for measuring efficiency. The DEA results are also used to identify input or output variables that must be improved if the Decision-Making Unit (DMU) needs to improve efficiency in form of potential improvement.Findings − This study shows that Covid-19 had an impact on decreasing the efficiency level of Indonesian and Malaysian Banks. This study also shows that Indonesian Banks are relatively efficient compared to Malaysian Banks. Nevertheless, Islamic bank is more affected by Covid-19 compared to conventional. In addition, the most important variable performance to be improved by banks during the Covid-19 pandemic is total financing.Implication − It can be used as a guideline for both nations to improve their shortcomings in each type of bank and to strengthen the banking system during economic downturns in order to speed up the recovery process.Originality − This is the initial study to examine the banking efficiency of Indonesia and Malaysia during the covid pandemic-induced economic crisis. As a result, it is expected to capture the impact of the covid-19 epidemic on banking efficiency.